The Shorter the Better? An Inverted U-Shape Relationship between Service Duration and Value Judgment in Efficiency-Focused Services - Ho, Liang-Chu; Chiou, Wen-Bin (Advances in Social Sciences Research Journal, 2018)
Consumers tend to evaluate services based on the time required to perform such services, when the value of the latter positively correlates with efficiency. This study investigated how consumers use the efficiency heuristic, referring to the tendency of consumers to infer the value of a service from the perceived efficiency with which it is performed. We studied 81 participants who had experienced car problems. The relationship between time devoted to a given service and judgments about its value showed a quadratic trend, with an inverted U-shape, in regard to a service in which value was related to efficiency. Specifically, participants judged services to be more valuable when they involved relatively moderate amounts of time to complete, compared to when they involved comparatively shorter or longer periods of time. The current research suggests that when a service was judged in terms of efficiency, consumers seemed to apply the efficiency heuristic not only to the time required for service performance, but also to labor costs.